Construction of MnO2@NH4MnF3 core-shell nanorods for asymmetric supercapacitor. (1st July 2020) - Li, Bin; Zhang, Xihua; Dou, Jinhe; Zhang, Pengxiang
Abstract: In this research, a facile method to produce the core-shell MnO2 @NH4 MnF3 nanorods of 50–80 nm in diameter from the manganese silicate particles was introduced. The α-MnO2 and NH4 MnF3 samples were synthesized and their electrochemical performances were also measured for comparison. TEM and EDS results show the ∼6 nm NH4 MnF3 shell is well coated on the α-MnO2 core. This novel nanocomposite has less Mn(II) and more Mn(IV) content, better conductivity, as well as moderate capacitive contribution. Besides, the specific capacitance of MnO2 @NH4 MnF3 nanorods reaches 240 F g −1 and could retain 98.0% of initial after 1000 cycles galvanostatic charge/discharge. The asymmetric supercapacitor AC//MnO2 @NH4 MnF3 with 1.7 V working potential range has been fabricated. It performs an energy density of 11.2 Wh kg −1 at the power density of 10 kW kg −1 .